Actual Problems of Application of IFRS in Belarus - Коротаев, С. Л. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The purpose of the study assessment, problem analysis and definition of prospects of harmonization of national accounting systems with International financial reporting standards (IFRS). The work examines the Genesis of IFRS in Belarus since 1998 to the present. In particular, the author highlights the peculiarities of national accounting systems do not take into account international approaches and allows to generate reliable financial statements by the entities of the Republic of Belarus. Special attention is focused on specific methods of accounting and write-offs exchange differences arising on foreign currency transactions, at the national peculiarities of formation of the cost of non-current assets and their depreciation. According to the results of the analysis of the findings on topical issues of application of IFRS in Belarus and specific proposals for harmonization of rules and principles IFRS with the national accounting and reporting. Along with the methodological problems discussed organizational issues of IFRS. Also assess the existing practice of audit statements prepared in accordance with IFRS, and provided suggestions to streamline such processes given the need to support national audit.